Hi there!
(a)
We can use the kinematic equation:
d = vit + 1/2at²
vi = initial velocity (0 m/s since the car starts from rest)
a = acceleration (m/s²)
t = time (sec)
Rearrange the equation to solve for acceleration:
d = 1/2at²
2d/t² = a
2(75)/(6²) = 150/36 = 4.167 m/s²
(B)
Now, that we know the car's acceleration, we can solve for its final velocity:
vf = vi + at (initial velocity = 0 m/s)
vf = at
vf = (4.167)(6) = 25 m/s
(C)
Now, we can use the equation:
distance = speed × time, or d = vt
Rearrange to solve for time:
d/v = t
85/25 = 3.4 sec